The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/car.2491
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Capacity to Change in High‐Risk Pregnant Women: A Pilot Study

Abstract: Pre-birth risk assessment is a process by which circumstances affecting an unborn child can be identified and support for mother and infant embedded. This mixed methods study describes a community-based pre-birth assessment and care pathway that utilised the Parents Under Pressure (PuP) programme to assess parenting capacity and provide support pre-and post-birth for 'at risk' women. Sixty-eight pregnant women referred to children's social care services were allocated to the pre-birth assessment and care pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Specifically, three heart rate measurements are used to calculate the step-up index. However, previous studies have reported considerable differences in the validity of using the step test index to evaluatė VO 2 max, with the corresponding correlation coefficient (R) being 0.35-0.94 (Buckley et al, 2004;Chang & Lin, 1995;Mazic et al, 2001;Su, Lin & Hsieh, 2006;Chang & Lin, 1995;Yoopat, Vanwonterghem & Louhevaara, 2002). Furthermore, step tests require the use of step-up boxes, and the overall test time must be at least 6 min to allow for heart rate recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, three heart rate measurements are used to calculate the step-up index. However, previous studies have reported considerable differences in the validity of using the step test index to evaluatė VO 2 max, with the corresponding correlation coefficient (R) being 0.35-0.94 (Buckley et al, 2004;Chang & Lin, 1995;Mazic et al, 2001;Su, Lin & Hsieh, 2006;Chang & Lin, 1995;Yoopat, Vanwonterghem & Louhevaara, 2002). Furthermore, step tests require the use of step-up boxes, and the overall test time must be at least 6 min to allow for heart rate recovery.…”
Section: Introductionmentioning
confidence: 99%
“…While there were acknowledged limitations to their study design, Harnett et al . () did find a distinctly different pattern of child protection outcomes for those infants whose mothers were part of the PuP programme compared to those receiving routine care. The quantitative data identified that many women on the PuP programme experienced significant improvements in wellbeing and perceived social support, and the qualitative data suggested perceived benefits of the programme among both the practitioners and the mothers involved.…”
Section: Peer‐on‐peer Abuse and Exploitationmentioning
confidence: 84%
“…Our final research paper in this issue from Paul Harnett et al . () takes us a stage further in evaluating an intervention designed to address an important disconnect in relation to mothers and infants considered high risk during pregnancy. Recognising that ‘despite their vulnerabilities, ‘at risk’ infants are often not given adequate protection within a time frame that is consistent with their developmental needs’ (Harnett et al ., , p. 73), Harnett and colleagues used a quasi‐experimental research design to evaluate the impact of the Parents under Pressure (PuP) programme for high‐risk families with potential or current involvement in child protection services.…”
Section: Peer‐on‐peer Abuse and Exploitationmentioning
confidence: 99%
“…More recently, two studies, one with maltreating parents (Van der Asdonk et al, 2020) and another with at very high-risk pregnant mothers (Harnett et al, 2018), tested a PCA protocol with an embedded video-feedback parent-child intervention to assess the potential for enhanced sensitivity, but mixed results were shown. The RCT study of Van der Asdonk et al (2020) showed that children of the target and control groups experienced similar recurrence rates of maltreatment 10 months after the intervention Also, evaluators of the target group did not feel more confident about their child placement recommendations.…”
Section: Assessing Parental Capacity To Change Using An Attachment Frmentioning
confidence: 99%